2002
DOI: 10.1056/nejmsa010285
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Trial of Inpatient and Outpatient Geriatric Evaluation and Management

Abstract: In this controlled trial, care provided in inpatient geriatric units and outpatient geriatric clinics had no significant effects on survival. There were significant reductions in functional decline with inpatient geriatric evaluation and management and improvements in mental health with outpatient geriatric evaluation and management, with no increase in costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
452
0
12

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 542 publications
(471 citation statements)
references
References 37 publications
7
452
0
12
Order By: Relevance
“…Similar results have been obtained in several subsequent studies, and although the results are not uniformly positive, aggregate analyses (of some 28 studies) demonstrate overall strong impact (Stuck, Siu et al 1993). The ability to produce sustained improvements in function is doubtful, but several studies have shown at least short term gains (Cohen, Feussner et al 2002). Careful patient selection is a critical factor in program effectiveness, with patients that are either too well, or severely ill (eg advanced dementia and terminal cancer) appearing to gain no benefit (Winograd 1991).…”
Section: Enhancing Treatment Outcomessupporting
confidence: 80%
“…Similar results have been obtained in several subsequent studies, and although the results are not uniformly positive, aggregate analyses (of some 28 studies) demonstrate overall strong impact (Stuck, Siu et al 1993). The ability to produce sustained improvements in function is doubtful, but several studies have shown at least short term gains (Cohen, Feussner et al 2002). Careful patient selection is a critical factor in program effectiveness, with patients that are either too well, or severely ill (eg advanced dementia and terminal cancer) appearing to gain no benefit (Winograd 1991).…”
Section: Enhancing Treatment Outcomessupporting
confidence: 80%
“…The FDP geriatrics content and design model were developed as follows: reviewing existing published geriatrics curricular materials, 5,6,8,18 including high-risk areas of geriatric hospital care; [19][20][21][22] drawing from the experience of the inpatient geriatric evaluation and treatment units; [23][24][25] and reviewing the Joint Commission mandates 26 that have a particular impact on the care of the older hospitalized patients (eg, high-risk medications, medication reconciliation, restraint use, and transitions of care). Final curricular materials were approved by consensus of the University of Chicago geriatrics/hospitalist core CHAMP faculty.…”
Section: Geriatrics Contentmentioning
confidence: 99%
“…23 In verschillende studies is gewezen op het belang van gespecialiseerde geriatrische afdelingen, vaak in combinatie met multidisciplinaire nazorg, zoals casemanagement na ontslag uit het ziekenhuis met revalidatiemogelijkheden. 19,[23][24][25][26] Ziekenhuisgerelateerd functieverlies bij oudere patiënten is een onderschat probleem. In Nederland zijn de medische behandeling en verpleegkundige zorg grotendeels gericht op de gediagnosticeerde ziekte, met weinig aandacht voor een reactiverende behandeling om functieverlies bij de oudere patiënt te voorkomen.…”
Section: Achtergrondunclassified